Antiplasmodial activity and genome mining study of marine-derived Streptomyces sp. GMY01 - Damayanti, Ema; Widada, Jaka; Dinoto, Achmad; Mustofa (Indonesian Journal of Pharmacology and Therapy, 2021)
High resistance to chloroquine in most malaria-endemic area in the world leads to the need for new antimalaria drugs. Marine bacterium Streptomyces is the source for potential new antimalarial molecules. This research aimed to investigate antiplasmodial activity of marine-derived of Streptomyces sp. GMY01 and to identify potential active compounds using genome mining study. In vitro antiplasmodial activity assays using flow cytometry method showed that the ethyl acetate extract of this bacterium had high antiplasmodial activity (IC50 value of 1.183 µg/mL) on Plasmodium falciparum FCR3. Genome mining analysis of whole-genome sequences using antiSMASH 6.0 beta version revealed that Streptomyces sp. GMY01 had 28 biosynthetic gene clusters (BGCs), including the genes encoding polyketide synthase, non-ribosomal peptide synthetase, terpene, lanthipeptide, bacteriocin, butyrolactone, ectoin, siderophore, and others. The known BGCs were predicted to be involved in the production of known compounds from gene clusters ranged from 5 to 100% similarity. Ongoing purification and elucidation of the structures will allow identification of the active compounds produced by marine-derived Streptomyces sp. GMY01.